The Critically Endangered western chimpanzee declines by 80%. Issue 9 (3rd July 2017) - Kühl, Hjalmar S.; Sop, Tenekwetche; Williamson, Elizabeth A.; Mundry, Roger; Brugière, David; Campbell, Genevieve; Cohen, Heather; Danquah, Emmanuel; Ginn, Laura; Herbinger, Ilka; Jones, Sorrel; Junker, Jessica; et al.
Abstract : African large mammals are under extreme pressure from unsustainable hunting and habitat loss. Certain traits make large mammals particularly vulnerable. These include late age at first reproduction, long inter‐birth intervals, and low population density. Great apes are a prime example of such vulnerability, exhibiting all of these traits. Here we assess the rate of population change for the western chimpanzee, Pan troglodytes verus, over a 24‐year period. As a proxy for change in abundance, we used transect nest count data from 20 different sites archived in the IUCN SSC A.P.E.S. database, representing 25, 000 of the estimated remaining 35, 000 western chimpanzees. For each of the 20 sites, datasets for 2 different years were available. We estimated site‐specific and global population change using Generalized Linear Models. At 12 of these sites, we detected a significant negative trend. The estimated change in the subspecies abundance, as approximated by nest encounter rate, yielded a 6% annual decline and a total decline of 80.2% over the study period from 1990 to 2014. This also resulted in a reduced geographic range of 20% (657, 600 vs. 524, 100 km 2 ). Poverty, civil conflict, disease pandemics, agriculture, extractive industries, infrastructure development, and lack of law enforcement, are some of the many reasons for the magnitude of threat. Our status update triggered the uplisting of the western chimpanzee to "Critically Endangered" on the IUCN Red List. In 2017, IUCN will start updating the 2003 Action Plan for western chimpanzees and will provide a consensus blueprint for what is needed to save this subspecies. We make a plea for greater commitment to conservation in West Africa across sectors. Needed especially is more robust engagement by national governments, integration of conservation priorities into the private sector and development planning across the region and sustained financial support from donors. Abstract : Pan troglodytes verus has declined by 80% over 24 years due poaching and habitat loss, its range was reduced by 20% from 657, 600 to 524, 100 km 2, and about 35, 000 chimpanzees now remain.